Unification of central concepts in education and research activity in pedagogical sciences - PANICO, Vasile (Acta et Commentationes, Sciences of Education, 2025)
This article analyses the relationships between the central concepts applied in educational practice and research in pedagogical sciences: the unity and specificity of education and training. These two phenomena are oriented towards the preparation and inclusion of the human being in social life. Training is an activity of preparing the personality for life by transmitting and accumulating social experience, and education aims at the direct and intentional inclusion of the personality in social life—the relationships of socialization and education. The central relationship of socialization is the connection between society and personality. It is largely distanced from the particularities and biopsychic specificity of the personality; the fundamental educational interaction in practical activity is between the educator/educational agent and the educated/self-educated. In research activity the central interaction is the relationship between the pedagogue researcher and the educational process; the educational environment is a set of circumstances that permanently besiege the life of the personality from a value perspective.